The efficiency of high-level water collecting cooling tower with the installation of cross wall affect by the evolution of aerodynamic field. (October 2019) - Chen, Guangan; Zhao, Yuanbin; Li, Wendong; Ge, Wenjing
Highlights: The evolution characteristic of the aerodynamic field below HWCDs was studied. The impact of aerodynamic field on the tower cooling performance was clarified. The effects of cross wall on the tower performance were comprehensively expounded. The range of optimum cross wall porosity and relevant impact factors were found. The reason of different impermeable wall effect in HNDWCT and UNDWCT was analyzed. Abstract: The aerodynamic field around high-level water collecting natural draft wet cooling tower (HNDWCT), especially that below its special high-level water collecting devices (HWCDs), strongly affects the tower efficiency. Therefore, the aerodynamic fields below HWCDs and its evolution characteristics have been studied, then the corresponding impact on the performance of HNDWCT has been clarified in detail. The results demonstrate that the incidence angle and speed of crosswind have great influence on the air flow state below HWCDs, thus the air distribution in heat and mass transfer zones and air mass flow rate through tower, resulting in the degradation of tower cooling performance. To mitigate the adverse effect of crosswind on tower cooling performance, cross wall has been investigated as a means to improve tower air flow structure. It has been found that the cross wall with appropriate porosity is beneficial to increase the tower efficiency. While, the optimum porosity depends on the crosswind speed and its incidence angle, which ranges from approximately 0.33–0.53. Furthermore, the structure of heat and mass transfer zones of HNDWCT, especially the rain zone, are different with that of usual natural draft wet cooling tower (UNDWCT), which causes the different effect of impermeable cross wall.